EDGE2D-EIRENE predictions of molecular emission in DIII-D high-recycling divertor plasmas. (May 2019) - Groth, M.; Hollmann, E.M.; Jaervinen, A.E.; Leonard, A.W.; McLean, A.G.; Samuell, C.M.; Reiter, D.; Allen, S.L.; Boerner, P.; Brezinsek, S.; Bykov, I.; Corrigan, G.; et al.
Highlights: This paper presents analyses of deuterium atomic and molecular emission and their contribution to the total radiation in DIII-D high-recycling ohmic plasmas:. Measurements of Lyman-alpha intensity and Lyman-Werner bands (attempted) in DIII-D divertor plasma utilizing new divertor SPRED. In high-recycling conditions, measured Fulcher-alpha band intensity 100x lower than Dalpha line intensity indicating negligible role of molecular radiation. In high-recycling conditions, EDGE2D-EIRENE predicts measured peak electron temperature, but broader profiles; measured electron density is underpredicted by simulations by 2–3x. Standalone EIRENE predictions, upgraded for calculations of Lyman-Werner intensities, predicted 50x lower Lyman-Werner band emission than Ly-alpha emission, corroborating negligible role of molecular emission in high-recycling conditions. Abstract: The contributions of deuterium molecular emission to the total deuterium radiation was assessed in DIII-D ohmically-confined plasmas in high-recycling divertor conditions. Radial profiles of the deuterium Ly-α line intensity across the low-field side divertor leg were obtained with the recently installed divertor Survey Poor Resolution, Extended Spectrometer [1]. A high-resolution spectrometer was used to measure the poloidal profiles of the deuterium Balmer-α and the deuterium Fulcher-α band intensity in the visible wavelength range. The scrape-off layer plasma and neutral distributions were simulated using the edge fluid EDGE2D-EIRENE [2], and the numerical solutions constrained utilizing Thomson scattering and Langmuir probe measurements at the low-field side midplane and the divertor target plate. The studies show that for these conditions molecular emission plays a negligible role in the total radiative power balance of the low-field side divertor, but molecular processes are important when evaluating deuterium Balmer-α line intensity for code-experiment validation.